Autism Spectrum Disorder and Associated Risk Factors: A Matched Case-Control Study - Maryam Mohammadian-Khoshnoud; Tahereh Omidi; Nasrin Shirmohammadi-Khorram; Jalal Poorolajal (Shahrekord University of Medical Sciences, 2019)
Background and aims: Despite substantial advances in the etiology of autism spectrum disorder (ASD), the environmental risk factors have not yet been well understood. The present study investigated the association between ASD, and maternal and perinatal risk factors. Methods: This matched, case-control study was conducted in Hamadan, the west of Iran, from November 2015 to May 2016. We enrolled 41 children with ASD aged 3-17 years. We selected four controls per one case from the same hospital where patients were born. Controls were separately matched with cases for sex, age, and birth year. Results: We compared 41 ASD cases with 164 controls. After adjusting the odds ratio (95% CI), ASD was significantly associated with third-degree relatives consanguinity [3.29 (1.39, 7.75)], short birth length [4.99 (1.15, 21.60)], short head circumference [7.87 (1.48, 41.76), respiratory distress syndrome at birth 3.97 (1.91, 8.22)], respiratory assistance at birth [2.92 (1.39, 6.10)], birth hypoxia [2.85 (1.35, 5.99)], and low 1-minute Apgar score [3.65 (1.04, 12.75)]. Conclusions: Our findings suggest that ASD may be associated with multiple maternal and perinatal risk factors. Evidence based on large prospective multicenter cohort studies is required to indicate the impacts of maternal and perinatal exposures.